SPEAKING ANXIETY IN EFL CLASSROOM: CATEGORIES AND FACTORS - Suciati Suciati (Universitas Islam Nahdlatul Ulama Jepara, 2020)
English is as foreign language for Indonesian students. Hence, they often find the anxiety in learning speaking. This study investigated the categories and factors of students’ anxiety in English as Foreign Language (EFL) classrooms. This is a case study. It was conducted at IAIN Kudus, especially in speaking classes of the second semester students, English Education Department (EED) in the academic year of 2018/2019. For obtaining the data, the researcher used observation of the class interaction and interview. Based on the analysis, there were two results. The speaking anxiety categories found in EFL classrooms are trait, state, and specific-situation anxiety. And, factors that cause the speaking anxiety are cognitive, affective, and performance factors.